Integrating Humanising Aspects into Urban Design: A Comprehensive Framework for Enhancing Quality of Life in Jeddah City - Ahmed Mohamed Refaat; Shahad Ghazoliy; Hosam Salah El Samaty; Ahmed Abd Elaziz Waseef (Urban Science)
“Humanising cities” is a significant topic in recent urban discussions, driven by diverse applications among urban managers and decision-makers. The Saudi Arabia initiative, through a quality-of-life programme, exemplifies efforts to integrate humanising aspects into urban projects. This study develops a structured multidimensional framework linking humanising aspects with quality-of-life indicators. Its significance is verified through the literature and a descriptive survey method in Jeddah’s neighbourhoods, considering residents’ preferences. This framework incorporates physical, social, environmental, and mobility indicators in the design of open spaces, prioritised based on user preferences. The framework offers significant potential to revitalise vacant neighbourhoods resulting from recent demolitions in Jeddah, restore the humanising aspects, improve the quality of life, and mitigate traffic congestion in northern areas through the “environmental” and “physical” indicators that share the highest priority based on the core findings of this research. Moreover, demographic factors, particularly age and education, significantly influence users’ preferences in humanising urban spaces.